2020
DOI: 10.1093/gerona/glaa187
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Cognitive and Motor Function Between Ages 45 and 90 Years: A Population-Based Study

Abstract: Background To establish trajectories of cognitive and motor function, and to determine the sequence of change across individual tests in community-dwelling individuals aged 45-90 years. Methods Between 1997-2016, we repeatedly assessed cognitive function with five tests in 9,514 participants aged 45-90 years from the population-based Rotterdam Study. Between 1999-2016, we measured motor function with three tests in 8,297 part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 60 publications
2
23
0
Order By: Relevance
“…Besides, our study has revealed several key determinants of heterogeneous cognitive trajectories. Among them, advanced age, low education level and cognitive reserve, as the most commonly identified risk factors of dementia, have been shown to be important predictors of faster cognitive decline [8,22,43,51]. In addition to baseline cognitive function, a notable difference in physical function was also observed across trajectory groups: older adults with IADL deficits tended to have a higher risk of being on the rapid decline trajectory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, our study has revealed several key determinants of heterogeneous cognitive trajectories. Among them, advanced age, low education level and cognitive reserve, as the most commonly identified risk factors of dementia, have been shown to be important predictors of faster cognitive decline [8,22,43,51]. In addition to baseline cognitive function, a notable difference in physical function was also observed across trajectory groups: older adults with IADL deficits tended to have a higher risk of being on the rapid decline trajectory.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although cognitive deterioration has been reported to be associated with several functional deficits such as frailty [17], falls [18], rapid eye movement behavior disorders (RBD) [19], depression [20], motor cognitive risk syndrome (MCR) [21] and etc., it remains undetermined whether cognitive ageing trajectory is associated with these functional deficits as well. Likewise, previous efforts which probed into factors shaping cognitive ageing trajectories were limited by small sample size, specific risk factors, or conflicting results primarily from western populations [8,9,11,[22][23][24]. A vast number of factors remain untested among Chinese older adults on this issue.…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive decline is associated with ageing and in some cases, it can lead to loss of independence and dementia [3,4]. However, as with most aspects of ageing, individual mobility and cognitive trajectories are extremely heterogeneous [2,5,6], dependent on the aspect of mobility or cognition being measured [6], and a product of multiple behavioural factors and biological mechanisms that occur and accumulate over a lifetime [1,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Previous findings in this area have been inconsistent and most studies do not report significant differences in the rate of cognitive decline due to educational attainment [ 11 , 17 ]. Although two previous studies found steeper cognitive decline in Verbal Memory, Processing Speed, and Verbal Fluency among those with higher education [ 20 , 21 ], results were inconsistent in a recent population study finding higher education to be associated with less steep decline on three attention and memory tests, but steeper decline for three other tests within the same domains [ 35 ]. These results are corroborated by the inconsistent findings reported in a review [ 11 ] and in a recent meta-analysis [ 17 ] finding substantial heterogeneity and no significant association with education for decline in six cognitive domains, including global cognition.…”
Section: Discussionmentioning
confidence: 99%